Role of ecology and phylogeny in determining tapeworm assemblages in skates (Rajiformes). Issue 6 (12th September 2018) - Beer, A.; Ingram, T.; Randhawa, H.S.
Abstract: An understanding of the mechanisms that determine host and parasite relationships is a central aim in parasitology. Association of a parasite species with a host species may be influenced primarily by phylogenetic constraints that cause parasite species to co-speciate with their host species, or predominantly by ecological parameters that influence all other co-evolutionary scenarios. This study aimed to investigate the role of co-speciation as well as other co-evolutionary scenarios in influencing the assemblages of tapeworm parasites (marine cestodes) in skate hosts (Rajiformes) using a modification of the PACo (Procrustean Approach to Cophylogeny) method. The study found that phylogeny and host ecology are both significant predictors of skate–tapeworm relationships, implying that co-speciation as well as other co-evolutionary scenarios are shaping these associations. The study also investigated the key ecological parameters influencing host-switching and found that host diet, distribution depth, average body size and geographical location have a combined effect. Given the importance of parasites in ensuring healthy and stable marine ecosystems, the findings of this study have implications for conservation management worldwide.